2009
DOI: 10.1037/a0015858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating model fit for growth curve models: Integration of fit indices from SEM and MLM frameworks.

Abstract: Evaluating overall model fit for growth curve models involves 3 challenging issues. (a) Three types of longitudinal data with different implications for model fit may be distinguished: balanced on time with complete data, balanced on time with data missing at random, and unbalanced on time. (b) Traditional work on fit from the structural equation modeling (SEM) perspective has focused only on the covariance structure, but growth curve models have four potential sources of misspecification: within-individual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
164
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 70 publications
2
164
0
1
Order By: Relevance
“…For all models, omnibus Wald's tests indicated that the predictors had an overall effect. For final unconditional and conditional models, fit was assessed based on several indices, and all had acceptable fit such that SRMR < .05; CFI > .95; and RMSEA < .07 (Wu, West, & Taylor, 2009).…”
Section: Plan Of Analysesmentioning
confidence: 99%
“…For all models, omnibus Wald's tests indicated that the predictors had an overall effect. For final unconditional and conditional models, fit was assessed based on several indices, and all had acceptable fit such that SRMR < .05; CFI > .95; and RMSEA < .07 (Wu, West, & Taylor, 2009).…”
Section: Plan Of Analysesmentioning
confidence: 99%
“…For example, it is more straightforward in a multilevel model to accommodate individual variation in the timing of measurements at a given occasion and to allow for further levels of clustering. (Further discussion of the relative strengths of MLM and SEM approaches to growth curve modelling can be found in Ghisletta & Lindenberg (2004), MacCallum et al (1997), Steele (2008) and Wu, West, & Taylor (2009). )…”
Section: Bivariate Growth Curve Modelsmentioning
confidence: 99%
“…Many steps are needed to properly structure the data, and the SEM code quickly becomes unwieldy. In contrast, the HLM approach allows for simpler model specification, is computationally more efficient, and can easily be expanded to higher level growth models for manifest variables (Curran, 2003;Wu, West, & Taylor, 2009). A detailed comparison between HLM and SEM can be seen in Bauer (2003) and Curran (2003).…”
mentioning
confidence: 99%
“…In contrast, there is some agreement on the cut-off criteria of conventional fit indices based on the likelihood ratio test in SEM, such as RMSEA, CFI, and NNFI (TLI) (e.g., Hu & Bentler, 1999). However, since in SEM-based LGM the factor loadings are usually fixed at time points rather than freely estimated, and the fit of the model to the mean structure should be reflected as well, assessment of model fit by using conventional SEM-based fit indices should be cautious (Mehta & Neale, 2005;Wu et al, 2009). When every individual is observed at the same fixed set of time points (called "balanced") with no missing values (called "complete"), ML estimation is used; otherwise, FIML estimation is used (Wu et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation